2003
DOI: 10.1002/jbm.a.10417
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth on surface‐modified dental implants: An in vitro study

Abstract: A major consideration in designing dental implants is the creation of a surface that provides strong attachment between the implant and bone, connective tissue, or epithelium. In addition, it is important to inhibit the adherence of oral bacteria on titanium surfaces exposed to the oral cavity to maintain plaque-free implants. Previous in vitro studies have shown that titanium implant surfaces coated with titanium nitride (TiN) reduced bacterial colonization compared to other clinically used implant surfaces. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(64 citation statements)
references
References 37 publications
(53 reference statements)
4
58
0
2
Order By: Relevance
“…In vitro and in vivo results show that TiN coatings do not have an adverse effect on this vital property. In vitro studies demonstrated that cell adhesion was no different between coated and uncoated Ti surfaces employing either mouse [24] or human gingival fibroblasts [25], while proliferation of human osteoblasts increased on TiNO x -coated titanium surfaces compared to uncoated controls [3]. Similar results were found by other studies applying bone marrow human mesenchymal stem cells [38] and bone marrow human stromal cells [4].…”
Section: Coatings In Implant Dentistrysupporting
confidence: 78%
“…In vitro and in vivo results show that TiN coatings do not have an adverse effect on this vital property. In vitro studies demonstrated that cell adhesion was no different between coated and uncoated Ti surfaces employing either mouse [24] or human gingival fibroblasts [25], while proliferation of human osteoblasts increased on TiNO x -coated titanium surfaces compared to uncoated controls [3]. Similar results were found by other studies applying bone marrow human mesenchymal stem cells [38] and bone marrow human stromal cells [4].…”
Section: Coatings In Implant Dentistrysupporting
confidence: 78%
“…As stated by Groessner-Schreiber et al [14] and Eisenbarth et al [9] cell morphology changes during adhesion to different surfaces. Ideally, cells flatten onto the material's surface, extend filopodia and form focal adhesion sites.…”
Section: Diskussionmentioning
confidence: 70%
“…MG63 human osteoblast-like cell lines were found to attach with high affinity to the sample surfaces in the order of hydroxyfluoride coated, TiN coated, smooth Ti, diamondlike carbon coated, SLA (sandblasted large grit and acid etched) treated, and hydroxyapatite thin coated surfaces [46]. An in vitro study with mouse fibroblasts had revealed that MTT activities and total protein contents were significantly increased on TiN coated polished Ti surfaces compared to the thermally oxidized and laser radiation structured surfaces [47]. In another study, glass sheets coated with Ti and TiN presented the highest number of focal adhesion contacts (FACs) of human gingival fibroblasts as a proof of good adhesion [48].…”
Section: Discussionmentioning
confidence: 99%